Recent Advances in Developing Artificial Autotrophic Microorganism for Reinforcing CO2 Fixation - Liang, Bo; Zhao, Yukun; Yang, Jianming (Frontiers in Microbiology, 2020)
With the goal of achieving carbon sequestration, emission reduction and cleaner production, biological methods have been employed to convert atmospheric carbon dioxide (CO2) into fuels and chemicals. However, natural autotrophic organisms are not suitable cell factories due to their poor carbon fixation efficiency and low biomass. Heterotrophic microorganisms are promising candidates, since they have been proven to be efficient biofuel and a chemical production chassis. This review first briefly summarizes six naturally occurring CO2 fixation pathways, and then focuses on recent advances in artificially designing efficient CO2 fixation pathways. Moreover, this review discusses the transformation of heterotrophic microorganisms into hemiautotrophic microorganisms and delves further into fully autotrophic microorganisms (artificial autotrophy) by use of synthetic biological tools and strategies. Rapid developments in artificial autotrophy have laid a solid foundation for the development of efficient carbon fixation cell factories. Finally, this review highlights future directions towards large-scale applications. Artificial autotrophic microbial cell factories need further improvements in terms of CO2 fixation pathways, reducing power supply, compartmentalization and host selection.